91.5k views
1 vote
Let me know the answer plz

Let me know the answer plz-example-1
User IlyaSurmay
by
5.1k points

2 Answers

0 votes

Answer:

J

Explanation:

Find the common ratio r of the geometric sequence then multiply a term by r to obtain the next term

r =
(a_(2) )/(a_(1) ) =
(6)/(-36) = -
(1)/(6)

The next 3 terms are


(1)/(6) × -
(1)/(6) = -
(1)/(36)

-
(1)/(36) × -
(1)/(6) =
(1)/(216)


(1)/(216) × -
(1)/(6) = -
(1)/(1296)

User Eric Melski
by
5.9k points
2 votes

Answer:

J.
-(1)/(36),
(1)/(216),
-(1)/(1296)

Explanation:

We are given the following geometric sequence and we are to find its 8th term:


-36, 6, -1, (1)/(6),...

Here
a_1=-36 and common ratio
(r) = (-1)/(6)=(-1)/(6).

The formula we will use to find the next three terms is:

nth term =
a_1 * r^((n-1))

5th term =
-36 * (-1)/(6)^((5-1)) =
-(1)/(36)

6th term =
-36 * (-1)/(6)^((6-1)) =
(1)/(216)

7th term =
-36 * (-1)/(6)^((7-1)) =
-(1)/(1296)

User Quint Stoffers
by
5.7k points